Kill Show : a true crime novel - Sweren-Becker, Daniel (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2023)
"Sixteen-year-old Sara Parcell disappeared without a trace on a crisp April morning in Frederick, Maryland. Her tragic story was a national obsession and the centerpiece of a controversial TV docu-series that followed her disappearance in real time. But is it possible that everyone missed the biggest secret of all? Ten years after the events in question, the people who knew Sara best are finally ready to talk."--
Keywords: Teenage girls -- Crimes against -- Fiction; Abduction -- Fiction; Cold cases (Criminal investigation) -- Fiction; Missing children -- Fiction; True crime stories -- Fiction; Murder -- Fiction; Murder -- Investigation -- Fiction; Television crime shows -- Fiction; Documentary television programs -- Fiction; Frederick (Md.) -- Fiction; Maryland -- Fiction; Detective and mystery fiction